PERBEDAAN PENURUNAN TEKANAN DARAH PRA LANSIA PRE HIPERTENSI YANG DIBERI JUS TOMAT (Lycopersicum grandifilum) - Fadillah, Hari Yani; Afriyana Siregar, Tonny C. Maigoda, (Politeknik Kesehatan Kemenkes Bengkulu, 2017)
The research aims to know the effect of tomato juice on blood pressure in pre-elderly pre hypertension at Posbindu Puskesmas Nusa Indah Bengkulu City.The design of research was a quasi experiment include pre test post test. This population was all patients posbindu aged 45-59 years. Sampling of this research randomized block design of one factorial were 6 samples divided into treatment and control group. The data which have been analyzed using univariate and bivariate. From this research were obtained the results such as the mean of sistole blood pressure before and after intervention in treatment group p = 0,273 and diastole p = 0,27. Mean systole blood pressure control group p = 0.060 and diastole p = 2.14. Distribution of tomato juice (Lycopersicum grandifilum) did not given affect the decrease in blood pressure of systole diastole before and after intervention in pre-elderly pre hypertension. Whereas the difference in mean systole of blood pressure treatment and control group p = 0.935 and diastolic of blood pressure p = 0.678. There ware not difference in mean of blood pressure in the tomato juice treatment group and control of Vitamin C. The result concluded there were not effect of tomato juice (Lycopersicum grandifilum) on systolic of blood pressure in pre-elderly pre hypertension at Posbindu Puskesmas Nusa Indah Bengkulu City.